Deconstructing urban green justice and well-being: a multi-group structural equation modeling analysis based on the activity space perspective - Liu, Shaobo; Qi, Jialing; Yang, Yi; Huo, Wen; Li, Jiang; Chang, Yating; Peng, You (Frontiers in Public Health, 2025)
IntroductionAgainst the backdrop of a global shift toward greener cities, equitable access to urban green spaces has increasingly been recognized for its impact on residents’ well-being. However, most existing studies rely heavily on residential proximity, overlooking the role of individual activity space differences and their influence on perceived fairness and well-being.MethodsThis study, grounded in environmental justice theory and the activity space perspective, constructs and tests a structural equation model integrating green space quality, green space exposure, perceived social benefits, perceived green justice, and subjective well-being. Based on 524 survey responses collected in Changsha, China, a multi-group structural equation modeling (Multi-Group SEM) approach was employed to compare path differences among near-, mid-, and far-distance activity space groups.Results and discussionResults show that: (1) Urban green space quality significantly influences green space exposure and perceived social benefits, which in turn enhance residents’ perception of green justice and ultimately boost subjective well-being; (2) The pathways from “Green Space Quality → Green Space Exposure,” “Green Space Quality → Perceived Social Benefits,” and “Green Space Exposure → Perceived Green Justice” remain consistently significant across all activity groups, forming a stable core mechanism; (3) Green space exposure in the mid-distance group is more sensitive to economic conditions. By incorporating activity space segmentation, this study extends the micro-mechanism framework of environmental justice and subjective well-being. The findings provide empirical evidence for understanding the psychological impacts of green space equity on urban residents and offer theoretical support for precision-oriented green space planning and equity-focused policy interventions.